Ungkapan Larangan Masyarakat Lubuak Sariak Kenagarian Kambang Kecamatan Lengayang Kabupaten Pesisir Selatan - Rahmadani, Yelvi; Ermanto, Ermanto; Noveria, Ena (Universitas Negeri Padang, 2012)
The purpose of this article is (1) to describe and analyze the categories of prohibition expressions and (2) to describe and analyze the social function of the prohibition expressions used in Lubuak Lubuak Sariak Kenagarian Kambang Kecamatan Lengayang Kabupaten Pesisir Selatan. The data of this study is the expressions of prohibition in the language of Minangkabau. This research uses oral sources spoken by people in communication. The data is collected by using descriptive methods, recording techniques, and technical notes. The finding of this study is 90 prohibition expressions used by the people of Lubuak Sariak Kenagarian Kambang Kecamatan Lengayang Kabupaten Pesisir Selatan.